Impact of half-crown/two carbonyl:-Ca2+ metal ion interactions of a low molecular weight gelator (LMWG) on its fiber to nanosphere morphology transformation with a gel-to-sol phase transition - Maity, Arunava; Dey, Ananta; Si, Mrinal Kanti; Ganguly, Bishwajit; Das, Amitava (Soft Matter, 2018)
We report here a smart functional low molecular weight gelator (LMWG) L, containing an unusual metal ion coordination site, i.e. ``half-crown/two carbonyl''. The gelator L shows excellent gelation behavior with typical fibrillar morphology in acetonitrile, methanol and ethanol media. Upon Ca2+ ion binding with its ``half-crown/two carbonyl'' coordination site, the acetonitrile gel of L exhibits a fiber to nanosphere morphology transformation along with a gel-to-sol phase transition as confirmed by microscopic investigation and by direct naked eye visualization, respectively. The mechanism involved in this morphology transformation and gel-to-sol phase transition process was studied thoroughly with the help of computational calculations and various spectroscopic experiments and discussed.